Bioavailability and costs of once‐daily and twice‐daily tacrolimus formulations in de novo kidney transplantation. Issue 8 (2nd July 2018) - Glander, Petra; Waiser, Johannes; Kasbohm, Silke; Friedersdorff, Frank; Peters, Robert; Rudolph, Birgit; Wu, Kaiyin; Budde, Klemens; Liefeldt, Lutz
Abstract: The use of once‐daily tacrolimus in de novo kidney transplantation is increasingly common. Therefore, we were interested in bioavailability aspects of novel once‐daily tacrolimus (LCPT, Envarsus) and once‐daily tacrolimus extended‐release formulation (ER‐Tac, Advagraf) compared with twice‐daily immediate‐release tacrolimus (IR‐Tac, Prograf). Furthermore, we calculated the costs. Kidney allograft recipients on tacrolimus‐based immunosuppression within 2 clinical trials were included in a single‐center analysis. The tacrolimus formulations were compared with respect to daily doses, doses per body weight, trough levels, and concentration‐dose (C/D) ratio over 12 months. Intrapatient variability in trough levels and C/D ratios after 3 months was calculated. For the calculation of tacrolimus costs, German list prices were used. Eighty patients (21 with LCPT, 23 with IR‐Tac, and 36 with ER‐Tac) were analyzed. Pharmacokinetic comparisons revealed significantly higher bioavailability of LCPT at all visits. The variability of trough levels and C/D ratios in general was high and highest in LCPT patients. Different dose requirements translated into different costs. Median treatment costs during the first year were 7.825€ (IQR 6.195‐8.892€) for LCPT, 9.813€ (IQR 7.630‐16.832€) for IR‐Tac, and 9.838€ (IQR 7.503‐ 13.541€) for ER‐Tac (Kruskal‐Wallis test, P  = .003). The 3 tacrolimus formulations exhibit different dose requirements, exposure, and costs in favor of LCPT.